Wastewater antibody signatures reflect SARS-CoV-2 infection and immunization patterns in the population - Dhammika Leshan Wannigama; Mohan Amarasiri; Phatthranit Phattharapornjaroen; Cameron Hurst; Charin Modchang; John Giles; Jillian Gauld; Tanakorn Chantanasaro; Kazuhiko Miyanaga; Longzhu Cui; Stefan Fernandez; Hirotake Mori; et al. (Water Research, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Regional conservation genomics: insights and opportunities from northern Australia - Teigan Cremona; Brenton von Takach; Robyn Shaw; Alexander Carey; Bridget Campbell; Skye Cameron; Renee Catullo; Caroline Chong; Saul Cowen; Danielle Edwards; Emilie Ens; Tony Griffiths; et al. (Biodiversity and Conservation, 2025)
Biodiversity conservation in northern Australia is characterised by high endemism, data deficiency, and high Indigenous land tenure and population. The Northern Australia Conservation Genomics Forum brought together experts to explore current genetic research with particular emphasis on integration of genomics within conservation practices. We discuss the regional biodiversity of northern Australia, highlighting the unique biogeographic patterns, known and unknown species diversity, and ongoing threats such as habitat degradation, altered fire regimes, invasive species, and climate change. This article synthesises key themes from the forum, including the current application of genomics in conservation, gaps and areas of need and opportunity to advance species conservation in this sparsely populated, yet iconic region of Australia. We highlight the need to expand collaborative research partnerships across land tenures with Indigenous organisations, pastoralists, government and non-government organisations, which is crucial for the effective study and conservation of the region’s biodiversity. The paper identifies the challenges and opportunities in applying genomic data to conservation strategies and applied management, including species translocations and habitat management, while acknowledging the limitations and gaps in current research and collections. The insights from this forum emphasise the advantages in using genomics to inform conservation decisions, and the need for continued research and collaboration to protect northern Australia’s unique biodiversity.

The applicability of regional red list assessments for soil invertebrates: first assessment of five native earthworm species in Canada - Helen R. P. Phillips; George G. Brown; Sam W. James; Jérôme Mathieu; John Warren Reynolds; Maheshi E. Dharmasiri; Claire L. Singer; Maria J. I. Briones; Heather C. Proctor; Erin K. Cameron (Biodiversity and Conservation, 2025)
Earthworms (Annelida: Clitellata: Crassiclitellata) are prominent members of the soil community, important to many ecosystem functions. Despite this, and like many other soil invertebrates, they are rarely considered in conservation assessments, including the International Union for Conservation of Nature (IUCN) Red List assessments used to assess species’ extinction risk. To investigate the applicability of the IUCN Regional Red Listing protocol to soil invertebrates, we assessed the conservation status of five earthworm species native to Canada using this protocol and all available occurrence records. In Canada, no earthworm species have yet been assessed by the Committee on the Status of Endangered Wildlife in Canada (COSEWIC). Due to the lack of data on population sizes and their trends, all five species were assessed using their Extent of Occurrence (EOO) (Criterion B). One species was assessed as Vulnerable ( Arctiostrotus vancouverensis) , two were assessed in non-threatened categories ( A. perrieri and Sparganophilus tamesis ), and two were assessed as Data Deficient ( A. fontinalis and Toutellus oregonensis ). For the majority, the main threats identified were the continuing loss of potential habitat due to land conversion and resource exploitation, as well as the effects of climate change. Increasing the amount of data, including but not limited to distribution and habitat preferences, would make the assessment process easier and status decisions better supported. By undertaking regional assessments for five native earthworm species in Canada, we show that Regional Red List assessments are feasible for soil invertebrates.

Australian subtropical vegetation and wetland response to fire, climate and nutrient availability during the Holocene - Haidee Cadd; Michela Mariani; John Tibby; Jonathan Tyler; Cameron Barr; Melanie J. Leng; Patrick Moss; Richard Lewis; Tim Cohen; Sam Marx; Glenn B. McGregor; Jonathan C. Marshall; et al. (Journal of Quaternary Science, 2025)
The iconic sand dune systems of Minjerribah (North Stradbroke Island), in southeastern Queensland, Australia, host numerous lakes and swamps containing organic‐rich sediment deposits that record changes in climate, fire and surrounding vegetation. Palaeoenvironmental reconstructions from individual locations can provide insights into changes in the environment, but determining the regional extent of these changes is seldom possible from a single site. Multi‐site compilations help elucidate the geographical nature of environmental changes and determine if they are driven by local or regional forces. Here, a synthesis of palynological records from six Minjerribah wetlands using a muti‐tiered Monte Carlo empirical orthogonal function (EOF) analysis allows island‐wide patterns of vegetation change to be identified. Coherent changes in vegetation were recorded, with first‐order changes (EOF1) indicating a long‐term shift in vegetation composition from closed forests towards woodland and heath vegetation. A compilation of macroscopic and microscopic charcoal from the same sites shares coherent patterns of change with a rainfall record from the island, suggesting that regional fire occurrence between 7000 and 2000 cal a bp was driven primarily by long‐term variations in rainfall and its influence on biomass. Comparison with fire activity, rainfall, sedimentary carbon, nitrogen and dust records from Minjerribah suggests that regional vegetation changes occur primarily in response to long‐term changes in nutrients and increasing rainfall variability. This analysis highlights the multi‐millennial connection between vegetation composition, climate, nutrients and fire occurrence across the Holocene in subtropical environments.

Genetic relatedness shapes social dynamics in a threatened finch: implications for population assessment - Mara F. Müller; Cameron J. Baker; Sam C. Banks; Mariana A. Campbell; Tara L. Crewe; Mirjam Kaestli; Sydney J. Collett; Ian J. Radford; Hamish A. Campbell (Animal Behaviour, 2025)

Impacts of ash-induced environmental alkalinization on fish physiology, and their implications to wildfire-scarred watersheds - Garfield T. Kwan; Trystan Sanders; Sammuel Huang; Kristen Kilaghbian; Cameron Sam; Junhan Wang; Kelly Weihrauch; Rod W. Wilson; Nann A. Fangue (Science of The Total Environment, 2024)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

The distribution of mountain hares and the possible effects of woodland expansion using the Cairngorm National Park as a case study - Scott Newey; Cameron Hubbard; Sam Gibbs; Jim McLeod; Adam Smith; Julie Ewald (European Journal of Wildlife Research, 2024)

Conducting volcanic ash cloud exercises: practising forecast evaluation procedures and the pull-through of scientific advice to the London VAAC - Frances Beckett; Sara Barsotti; Ralph Burton; Fabio Dioguardi; Sam Engwell; Matthew Hort; Nina Kristiansen; Sue Loughlin; Anton Muscat; Martin Osborne; Cameron Saint; John Stevenson; et al. (Bulletin of Volcanology, 2024)
The London Volcanic Ash Advisory Centre (VAAC) provides forecasts on the expected presence of volcanic ash in the atmosphere to mitigate the risk to aviation. It is fundamentally important that operational capability is regularly tested through exercises, to guarantee an effective response to an event. We have developed exercises which practise the pull-through of scientific advice into the London VAAC, the forecast evaluation process, and the decision-making procedures and discussions needed for generating the best possible forecasts under real-time conditions. London VAAC dispersion model forecasts are evaluated against observations. To test this capability in an exercise, we must create observation data for a hypothetical event. We have developed new methodologies for generating and using simulated satellite and lidar retrievals. These simulated observations enable us to practise our ability to interpret, compare, and evaluate model output and observation data under real-time conditions. Forecast evaluation can benefit from an understanding of how different choices of model setup (input parameters), model physics, and driving meteorological data impact the predicted extent and concentration of ash. Through our exercises, we have practised comparing output from model simulations generated using different models, model setups, and meteorological data, supplied by different institutions. Our exercises also practise the communication and interaction between Met Office (UK) scientists supporting the London VAAC and external experts, enabling knowledge exchange and discussions on the interpretation of model output and observations, as we strive to deliver the best response capability for the aviation industry and stakeholders. In this paper, we outline our exercise methodology, including the use of simulated satellite and lidar observations, and the development of the strategy to compare output generated from different modelling systems. We outline the lessons learnt, including the benefits and challenges of conducting exercises which practise our ability to provide scientific advice for an operational response at the London VAAC.

Conservation prioritisation of genomic diversity to inform management of a declining mammal species - Brenton von Takach; Skye F. Cameron; Teigan Cremona; Mark D.B. Eldridge; Diana O. Fisher; Rosemary Hohnen; Chris J. Jolly; Ella Kelly; Ben L. Phillips; Ian J. Radford; Kate Rick; Peter B.S. Spencer; et al. (Biological Conservation, 2024)

Population genomics of a predatory mammal reveals patterns of decline and impacts of exposure to toxic toads - Brenton von Takach; Louis Ranjard; Christopher P. Burridge; Skye F. Cameron; Teigan Cremona; Mark D. B. Eldridge; Diana O. Fisher; Stephen Frankenberg; Brydie M. Hill; Rosemary Hohnen; Chris J. Jolly; Ella Kelly; et al. (Molecular Ecology, 2022)
Mammal declines across northern Australia are one of the major biodiversity loss events occurring globally. There has been no regional assessment of the implications of these species declines for genomic diversity. To address this, we conducted a species‐wide assessment of genomic diversity in the northern quoll ( Dasyurus hallucatus ), an Endangered marsupial carnivore. We used next generation sequencing methods to genotype 10,191 single nucleotide polymorphisms (SNPs) in 352 individuals from across a 3220‐km length of the continent, investigating patterns of population genomic structure and diversity, and identifying loci showing signals of putative selection. We found strong heterogeneity in the distribution of genomic diversity across the continent, characterized by (i) biogeographical barriers driving hierarchical population structure through long‐term isolation, and (ii) severe reductions in diversity resulting from population declines, exacerbated by the spread of introduced toxic cane toads ( Rhinella marina ). These results warn of a large ongoing loss of genomic diversity and associated adaptive capacity as mammals decline across northern Australia. Encouragingly, populations of the northern quoll established on toad‐free islands by translocations appear to have maintained most of the initial genomic diversity after 16 years. By mapping patterns of genomic diversity within and among populations, and investigating these patterns in the context of population declines, we can provide conservation managers with data critical to informed decision‐making. This includes the identification of populations that are candidates for genetic management, the importance of remnant island and insurance/translocated populations for the conservation of genetic diversity, and the characterization of putative evolutionarily significant units.

Quantifying the differences in avian attack rates on reptiles between an infrastructure and a control site - Cameron Law; Lesley Lancaster; Jeanette Hall; Sam Handy; Mike Hinchliffe; Clare O’Brien; Katie O’Brien; Sam Watts; David O’Brien (European Journal of Wildlife Research, 2020)

Uncertainty, Irreversibility and the Optimal Timing of Large-Scale Investments in Protected Species Habitat Restoration - Cameron Speir; Sam Pittman; David Tomberlin (Frontiers in Marine Science, 2015)

Asynchrony from synchrony: long-range gamma-band neural synchrony accompanies perception of audiovisual speech asynchrony - Sam M. Doesburg; Lauren L. Emberson; Alan Rahi; David Cameron; Lawrence M. Ward (Experimental Brain Research, 2008)